How evidence conflict affects willingness to avoid health information: from the perspective of compensatory control theory - Zhai, Jiajing; Ou, Jiaqi; Nie, Jinghong (Frontiers in Communication, 2025)
This study investigates how conflicting health evidence shapes cancer-screening information avoidance through the lens of compensatory control theory. We conducted a 5 × 2 between-subjects online experiment (Credamo, China; N = 372, 67% female; Mage = 30.4) in which participants were randomly assigned to read thyroid-screening articles that manipulated evidence conflict (no conflict, statistical conflict, anecdotal conflict, or cross-valence: statistics-support/anecdotes-oppose vs. anecdotes-support/statistics-oppose) and perceived disease control (high vs. low). The dependent variable was health-information avoidance, with message elaboration and ambiguity aversion as mediators. Moderated mediation analyses revealed a clear defensive pathway under low perceived control: conflict increased ambiguity aversion, which in turn increased avoidance (indirect effect = 0.025, 95% CI [0.007, 0.045]). In contrast, the hypothesized engagement pathway via increased elaboration under high control was not supported in the overall model, although a positive relationship between conflict and elaboration was observed in the high-control group. These findings suggest that perceived control shapes whether conflict prompts deeper engagement or defensive withdrawal. Practically, communicators may reduce avoidance by aligning anecdotal and statistical cues—or by embedding control-boosting frames—when targeting low-control audiences.